2019
DOI: 10.1111/bcp.13985
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of patient‐reported outcomes associated with the use of direct‐acting oral anticoagulants

Abstract: Patient-reported outcomes (PROs) are a distinctive method of evaluating patient response to health care or treatment. This systematic review aimed to analyse the impact of PROs in patients on direct oral anticoagulant (DOAC) treatment, prescribed for any indication (e.g. venous thromboembolism treatment or atrial fibrillation) using controlled trials (CT) and real-world observational studies (OS).Methods: A systematic search of articles was conducted according to PRISMA guidelines using databases, with the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 61 publications
(101 reference statements)
2
36
0
Order By: Relevance
“…This study explores some key challenges facing patients with AF and the healthcare professionals prescribing and managing their treatment, which were largely consistent with those identified previously. 6 25 36 However, multistakeholder focus groups offer depth by providing multiple individual perspectives by giving them a voice. While anticoagulation therapy for patients with AF using NOACs is widely adopted and is diffusing into routine practice significant operationalisation issues and barriers to effective treatment/management persist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study explores some key challenges facing patients with AF and the healthcare professionals prescribing and managing their treatment, which were largely consistent with those identified previously. 6 25 36 However, multistakeholder focus groups offer depth by providing multiple individual perspectives by giving them a voice. While anticoagulation therapy for patients with AF using NOACs is widely adopted and is diffusing into routine practice significant operationalisation issues and barriers to effective treatment/management persist.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Ireland, a survey of general practitioners (GP) identified lack of integration between primary and secondary care and knowledge gaps among prescribers with regard to prescribing decision-making and managing patients with AF prescribed NOACs (in the absence of INR monitoring requirements). [20][21][22] While there is an abundance of evidence from systematic trials and meta-analysis on the efficacy and effectiveness of safety of oral anticoagulation therapy in the management of AF, there is limited qualitative evidence capturing both the clinicians 25 and patients' views 6 simultaneously. Generating qualitative evidence provides the opportunity to add depth and ensuring focus on patient-level care.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…There is substantial clinical experience with use of DOACs, and patient-reported outcomes have been summarized in a systematic review ( 28 ). In addition, clinical trials have found that the newer oral anticoagulants can reduce the stroke rate by 19% compared with warfarin ( 11 , 29 ).…”
Section: A Comparison Of Doacs and Vkasmentioning
confidence: 99%